Introduction to geography : people, places, and environment - Bergman, Edward F. (Prentice Hall, 1999)
Three themes in this textbook: Geography Explores the Interrelationships between Humankind and the Environment. Human Geography is not restricted to the Study of Exotic Lands and Poeples. And Modern Geography is Dynamic.